Pengaruh Stres Kerja Dan Motivasi Kerja Terhadap Produktivitas Karyawan Pada Coffe Comunitas Di Tenggarong - Putri, Vidya Aulia; Askiah, Askiah; Hadiyanti, Sofia Ulfa Eka (STIE AMKOP, 2025)
This study examines the influence of work stress and work motivation on employee productivity at Coffe Comunitas in Tenggarong. The background of this study stems from the importance of human resources in supporting organizational productivity, particularly in service industries such as cafes, which rely heavily on service quality. The issues examined are: Do work-related stress and work motivation affect employee productivity at Coffe Comunitas? This study is unique because it focuses on the local micro-business sector, which has not been extensively researched, especially in the context of work-related stress and motivation. The method used is quantitative research with a total sample of 30 employees using a questionnaire as the data collection instrument. Analysis was conducted using multiple linear regression through SPSS. The results of the study indicate that work stress has a negative and significant effect on productivity, while work motivation has a positive and significant effect. Simultaneously, both variables influence productivity by 76.4%. The conclusion of this study is the importance of management in reducing work stress and increasing motivation to support employee productivity. The implication is that companies need to create a supportive work environment and provide appropriate rewards for employees. Keywords: Work Stress, Work Motivation, Employee Productivity